Availability of Antibiotics for Veterinary Use on the Internet: A Cross-Sectional Study - Garcia, Juan F.; Diez, M. Jose; Sahagun, Ana M.; Diez, Raquel; Sierra, Matilde; Garcia, Juan J.; López, Cristina; Fernandez, M. Nelida (Frontiers in Veterinary Science, 2022)
The misuse or overuse of antibiotics can favor the emergence of antimicrobial resistance, with a direct impact on human and animal health as well as on ecosystems. In this work we have analyzed the web pages in which antibiotics for veterinary use can be purchased online. By using a specifically developed software, we carried out a detailed search to know if each individual antibiotic and the families included in the OIE list of antimicrobial agents of veterinary importance (in English and in Spanish) were sold, reviewing the offers according to the administration route and the species to which antibiotics were intended. The greatest offer of antibiotics was for those compounds considered critically important by OIE. In the search in English, penicillins were available on 55.8% of the sites, tetracyclines on 55.0% and fluoroquinolones on 52.7%. In Spanish, the families with the greatest presence were fluoroquinolones (67.9% of the sites), tetracyclines (67.9% of the sites) and penicillins (65.4% of the sites). Regarding individual antibiotics, the most offered in both searches were amoxicillin (49.6% of the sites in English and 57.7% in Spanish) and doxycycline (46.5% of the sites in English and 53.8% in Spanish). Most offers were for oral and parenteral administration and intended for cats and dogs, and for bovines.